Perfluorinated fiber material properties following femtosecond laser inscription - Leal-Junior, Arnaldo; Theodosiou, Antreas; Fernandes, António José S.; Frizera, Anselmo; Kalli, Kyriacos; Marques, Carlos Alberto F. (My University, 2020)
This paper presents the materials analysis and comparison of fiber gratings inscribed using the plane-by-plane femtosecond laser method in cyclic transparent optical polymer (CYTOP) fibers at different angles. Specifically, the gratings were inscribed with 0°, 45° and 90° angle in respect to the core's optical axis. The materials molecular structures are investigated through the Fourier-transform infrared spectroscopy (FTIR) and Raman spectroscopy, which indicate that the changes on the material structure are highly controlled and restricted to the fiber core, as an important benefit of the plane-by-plane inscription method. In order to verify the impact of the grating inscription in the samples' physical properties, thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA) are performed. Results show an increase in the degradation temperature in higher inscription angles (90°), whereas there is no significant variation in the polymer glass transition temperature (Tg) between samples. However, the frequency shift on the polymer loss factor monotonically increases with the decrease of the grating angle, i.e., 0° sample shows the largest shift in the loss factor. Regarding the elastic modulus, the 90° inscription angle sample presents the lowest elastic modulus. The results obtained in these analyses provide guidelines on the fabrication and operation limits (in terms of temperature and stress) of POF based devices, including tunable filters and sensors.
Keywords: Polymer optical fibers; Optical materials; Femtosecond laser inscription